Association between Cell Microenvironment Altered by Gold Nanowire Array and Regulation of Partial Epithelial‐Mesenchymal Transition. (3rd December 2020) - Kim, Yu Jin; Ko, Min Jun; Park, Bum Chul; Moon, Jun Hwan; Jeon, Yoo Sang; Park, Hyeon Su; Kim, Myeong Soo; Kim, Hee‐Dae; Shin, Daiha; Kim, Young Keun
Abstract: Cell microenvironment is an essential factor in determining cell growth and cell fate. Many studies have been carried out to understand the functions and mechanisms of small molecules or growth factors/cytokines; however, the effects of the physical environment on cells are relatively unknown. Changes in the cell's physical microenvironment affect cell adhesion and modify intracellular signaling controlled by adhesion properties, resulting in altering the cytoskeletal structure and cellular properties. Herein, it is demonstrated that the changes in cell adhesion can affect the epithelial‐mesenchymal transition (EMT) of epithelial cells by implementing a cell microenvironment with a gold (Au) nanowire array to influence cell adhesion. A forcible decrease in cell adhesion leads to the downregulation of epithelial biomarkers and the upregulation of mesenchymal biomarkers. The results of force‐distance experiments using atomic force microscopy showed that the overall stiffness of epithelial cells declined similarly to the case for mesenchymal‐like cells. With this comprehensive analysis of cellular properties, a physical microenvironment for cell adhesion alteration is suggested, that can induce mesenchymal characteristics in both epithelial and mesenchymal cells through partial EMT. Abstract : Epithelial‐mesenchymal transition (EMT) is a primary process that occurs early in the metastasis of cancer. Alteration of the cell microenvironment by the nanowire array induces a change in the focal adhesion of the cell. Focal adhesion change acts as an external stimulus to the cell, resulting in inducing EMT. Partially transited epithelial cells exhibit physical properties similar to mesenchymal‐like cells.